Price dispersion in dynamic competition - Rafael R. Guthmann (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2020)
In product markets, there exists substantial dispersion in prices for transactions of physically identical goods, and incumbent sellers sell at higher prices than entrants. This study develops a theory of dynamic pricing that explains these facts as results from the same fundamental friction: Buyers are imperfectly aware of which sellers are operating, and the degree of awareness about a seller is ndogenous. The equilibrium is unique and efficient, and features randomized pricing strategies where incumbents post higher prices than entrants. If buyers' memory depreciation is low, then the equilibrium of the industry tends to approximate perfectly competitive conditions over time.
Keywords: C78; D11; D40; D83; 330; Buyer Awareness; Price Dispersion; Customer Capital; Industry Life Cycle; Information Frictions